ANALISIS PENGARUH INSENTIF PAJAK TERHADAP PENGHINDARAN PAJAK PERUSAHAAN (STUDI EMPIRIS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2011-2015) - Rombe, Astriditta; Rahardjo, Hartono; Hartanto, Susanna (Widya Mandala Surabaya Catholic University, 2017)
This study aims to prove empirically the disclosure of operating segments to investment risk. The object of research us-ing population of manufacturing companies listed in Indonesia Stock Exchange in the period 2011-2015. The sampling technique used purposive sampling technique based on predetermined criteria. The test results showed that tax incentive is positive the tax incentive the avoidance, with significant use of GAAP ETR but not significant using Current ETR. Debt to equity ratio is signif-icant the tax avoidance, while return on assets and firm size (size) does not affect the tax avoindance if using proxy GAAP ETR. The test results when viewed using proxy Current ETR find that the return on asset significant to tax evasion, while the debt to equity ratio and firm size (size) has no effect on tax avoidance.